TEACHER AGENCY IN THE IMPLEMENTATION OF DIFFERENTIATED LEARNING: AN INTERPRETIVE STUDY - Sella Ayu Nindya; Intan Rebecca Siburian; Istanti Hermagustiana; Dyah Sunggingwati (Journal of English Educational Study (JEES), 2023)
This research objective was to investigate teacher agency in the context of implementing differentiated learning which is one of the instructions from the latest national curriculum. The study employed an interpretive approach by exploring teacher agency usingthe ecological model of teacher agency with three dimensions: iterational, projective, and practical-evaluative. To capturean in-depth understanding of teacher agency, there are three main domains related: teaching planning, differentiated learning, and technology in pedagogy.The differentiated learning domain was selected to be investigated in this study. Data was gathered by interviewing a nineteen experiencedteacher who implemented differentiated learning in her teaching by the latest curriculum instruction. The collected data is analyzed using thematic analysis to identify patterns and insights regarding the perception of the teacher. The study uncovered that teacher agency wasshaped by past experiences and knowledge. Teacher’sinnovation in teaching and support for the success of national education goals indicated the dedication of teacher agency.This research showed that teachers committed to improving student learning and willing to face challenges are through teacher agency. Further research opportunities include exploring teachers' planning strategies and technology integration in teaching.